KEMAMPUAN PENALARAN ANALOGI MATEMATIS: SYSTEMATIC LITERATURE REVIEW - Dwi Agusantia; Dadang Juandi (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2022)
This study aims to describe the results of research on students' analogical reasoning abilities in learning mathematics. This study uses the Systematic Literature Review (SLR) method. The sample consisted of 17 articles from SINTA and Google Scholar indexed journals published from 2018 to October 2022. The results of this study were reviewed based on the journal index, year of publication, year of publication, journal index, level of study, sample size, research location, and material covered. used in research analysis of students' analogical reasoning abilities in learning mathematics. By using the SLR method, it was found that the most articles were published in SINTA 4, there was an increase in the number of articles published in SINTA each year, the sample size used was less than 30 subjects, the location was dominated by Java, algebra and geometry materials were mostly used. used in students' mathematical literacy research based on cognitive style, and in terms of the four components of analogical reasoning, namely encoding, inferring, mapping, and application it was found that there were still many students who had difficulty in the mapping and applying.